Vladimir Lossky's Involvement in the Dieu Vivant Circle and its Ecumenical Journal - Coman, Viorel ca. 20./21. Jh. (Irish theological quarterly, 2020)
Vladimir Lossky's theology has been extensively studied by scholars but his commitment to ecumenism still remains an insufficiently researched domain. This article fills this lacuna by shedding light on an important chapter of Lossky's ecumenical activity: his involvement in the Parisian Dieu Vivant circle and its ecumenical journal. The article argues that Lossky's editorial work for the Dieu Vivant journal represents an important episode of the ecumenical interactions between the representatives of the Orthodox Neo-Patristic movement and the architects of the French Catholic Ressourcement. Moreover, Lossky's willingness to be a member of the editorial board of the Dieu Vivant journal cannot be understood apart from the affinity which existed between his theological vision and the agenda of the French periodical: the priority of the eschatological consciousness of Christianity.